IDH3γ functions as a redox switch regulating mitochondrial energy metabolism and contractility in the heart - Nanadikar, Maithily S.; Vergel Leon, Ana M.; Guo, Jia; van Belle, Gijsbert J.; Jatho, Aline; Philip, Elvina S.; Brandner, Astrid; Böckmann, Rainer; Shi, Runzhu; Zieseniss, Anke; Siemssen, Carla M.; Dettmer, Katja; et al. (Nature Communications, 2023)
Redox signaling and cardiac function are tightly linked. However, it is largely unknown which protein targets are affected by hydrogen peroxide (H2O2) in cardiomyocytes that underly impaired inotropic effects during oxidative stress. Here, we combine a chemogenetic mouse model (HyPer-DAO mice) and a redox-proteomics approach to identify redox sensitive proteins. Using the HyPer-DAO mice, we demonstrate that increased endogenous production of H2O2 in cardiomyocytes leads to a reversible impairment of cardiac contractility in vivo. Notably, we identify the γ-subunit of the TCA cycle enzyme isocitrate dehydrogenase (IDH)3 as a redox switch, linking its modification to altered mitochondrial metabolism. Using microsecond molecular dynamics simulations and experiments using cysteine-gene-edited cells reveal that IDH3γ Cys148 and 284 are critically involved in the H2O2-dependent regulation of IDH3 activity. Our findings provide an unexpected mechanism by which mitochondrial metabolism can be modulated through redox signaling processes.
CRIS-Team Scopus Importer:2023-04-28